Social interaction game to promote empathy among first year medical students: a pilot study - Johnson, Liaquat R.; Raja, Ramiz (International Journal Of Community Medicine And Public Health, 2018)
Background: Empathy is integral to professionalism, but is lacking in medical students. There are few interventions that promote empathy. This pilot study describes the first use of a novel intervention to promote empathy. Methods: A novel social interaction game was developed and administered to first MBBS students. It provided an experiential simulation of persons belonging to lower socioeconomic strata over 4 simulated ‘days’. This cross-sectional study assessed the impact of the intervention on empathy using a 5-point Likert scale to score self-perceptions across several domains. The data were analyzed using repeated measures analysis of variance (RMANOVA). Results: There was a statistically significant decline in scale scores on all days following Day 1 (p<0.05). This was true across all domains. Cronbach’s alpha for internal reliability was 0.91 for Day 1; and 0.97 for Day 1 through Day 4. Open ended comments indicated empathic feelings were generated due to the intervention. Conclusions: A simulation experience like the social interaction game described here, may be used to improve the attitudes and empathy of medical students towards persons from low socioeconomic backgrounds.